Description of Neoperla yingshana sp. nov. (Plecoptera: Perlidae) from Hubei Province of China - Chen, Zhi-Teng; Du, Yu-Zhou (Zootaxa, 2017)
A new species of the genus Neoperla (Plecoptera, Perlidae), N. yingshana Chen & Du sp. nov. from the Wujiashan National Forest Park, Hubei Province of central China is described, illustrated and compared with similar taxa. The new species is characterized by the aedeagal tube long with an upcurved, finger-like spinulose lobe subapically, and by the aedeagal sac plump, gradually tapering to a blunt tip with dense spinules on ventral surface and granules surrounding sac apex.